N-Acyl Homoserine Lactones sebagai Signal Quorum Sensing untuk Meningkatkan Efektifitas Bakteri Fosfat - Tamad Tamad (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2014)
Phosphate bacteria (PB) are able to release P-adsorption by soil. PB  effectiveness in releasing adsorption P  controled by quorum sensing (QS) signal. PB  produces a QS signal  as N-acyl homoserine lactones (N-HSL). The aim of this study are to determine the type of N-HSL as QS signal of PB (Pseudomonas trivialis, P. putida and P. fluorescens) and find the source of N-HSL from root extracts of some plants (rice, corn, bamboo, banana and peanuts). Analysis of N-HSL using HPLC (Hitachi UV-VIS detector L-2420), L-2200 autosampler (20 mL), L-2130 pump and column C OOF-4250-CO/10 µm LaChrom Ultra 18 (2 µm) 100 A 150 x 4.60 mm 10 m KPOW 490065-1 (Phenomenex), temperature 60° C, flow rate of 0.9 mL/minute  and a gradient of 30-100 % in 1.0 minutes. Standard N-HSL  is C4-HSL, 6, 8, 10, 12 homoserine lactones (Sigma-Aldrich, Germany) was dissolved in acetonitrile (Merch, India) with a concentration of 50 mM. P-dissolved by PB determined by staining NVM and a spectrophotometer at a wavelength of 413 nm. PB population is determined by the OD (optical density) at a wavelength of 600 nm. PB  populations  on medium Pikovskaya influenced by PB isolates, the type of P sources and duration of incubation. N-HSL generated by PB highest is Butanoyl (C4) homoserine lactones. PB isolates 9 and Ca-phosphate sources produce N-HSL most. Root extract of rice, corn, bamboo, bananas and peanuts can be a source of   N-HSL. Soluble phosphorus from medium Pikovskaya influenced by the type of PB isolates and source of P.